PENGARUH INTENSITAS PERSEDIAAN, SALES GROWTH, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Kurtusi, Achmad Sadam; Angraini, Dila (LPPM Universitas Bina Bangsa, 2024)
This research aims to identify the influence of Inventory Intensity, Sales Growth, and Company Size on Tax Avoidance. The research population includes Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange during the period of 2018-2023. The sample, selected using purposive sampling, consists of 24 companies observed over 6 years. This study employs a quantitative method using secondary data and falls under the category of associative research. The data collection technique used is a documentary technique, involving the gathering of annual reports, financial statements, and other relevant data from existing documents. The results of the research indicate that Inventory Intensity, Sales Growth, and Company Size have a simultaneous effect on Tax Avoidance. Meanwhile partially, Inventory Intensity and Sales Growth do not affect Tax Avoidance, whereas Company Size effects Tax Avoidance